Home time. Book one, Under the river - Whyte, Campbell, 1984- (Top Shelf Productions, 2017)
In the last summer of their high school career, twins Lilly and David plan on relaxing with friends, holding sleepovers, playing fantasy games, and maybe finding romance--then they and their gang of friends fall in a river and sink through into a world of fantastic creatures, where they are called magical spirits, get threatened by lizards, and learn how to brew tea in their effort to get back home.